ANALISIS PEMAKAIAN PAYLAYTER PADA GENERASI Z - Gerry Alde Sitepu (2023)
Technological developments continue to develop continuously in e-commerce, especially in paylayer itself, all human needs can be easily fulfilled. Technological developments have also penetrated into payment methods or means of payment. One of the payment instruments that is very popular today is the paylater, which is known as shopping now, pay later, especially among Generation Z. This final project aims to find out the advantages and disadvantages of using and using paylayter itself with daily life in using the paylayter itself. by generation Z. The results of this final project show that the motive behind the use of paylater among generation Z is to make transactions easier, save time, offer lots of vouchers, be able to pay debt or get vouchers and cashback in installments, and make ends meet